Spray and Particle Characterization of a Spray Flame Synthesis Process using Wide-Angle Light Scattering (WALS) - Münsterjohann, Bettina; Aßmann, Simon; Huber, Franz; Will, Stefan (Proceedings of the Proceedings 9th European Combustion Meeting (ECM 2019), 2019)
Spray Flame Synthesis (SFS) is a promising technology to produce nanomaterials with well-defined functional properties. Since particle size and morphology have a significant influence on the properties of the synthesized nanoparticles, correlations between these parameters, the droplet size of the spray and process conditions are required. For this reason, Wide-Angle Light Scattering (WALS) is applied to a flame of a standardized SFS burner, which allows for both droplet and particle size evaluation. For the aggregate size Rg,eff, no significant influence of different dispersion gas flow rates on particle morphology is measured, while the droplet size d decreases with increasing dispersion gas flow rate